Education, Environment, and Digital Access to Financial Literacy through Self-Efficacy - Aji Prasetyo Suyono; Yulian Ade Chandra; Kartika Ayu Kinanti; Nayla Iftitah Despriana; Lisa Faradianti (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to examine the influence of financial education, family environment, and digital access partially on students' financial literacy, by placing financial self-efficacy as a mediating variable. Design/methodology/approach – This study employed a quantitative method with a survey approach through questionnaire distribution. Primary data were collected from the active student population in East Java. The sample was determined using the Lemeshow formula with a purposive sampling technique. Data analysis was conducted in stages using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through SmartPLS software to test the outer model, inner model, and hypothesis testing via bootstrapping. Finding/Results – The test results show that financial education has a positive and significant direct impact on students' financial literacy. Conversely, the direct influence of family environment and digital access was shown to be insignificant on students' financial literacy. The mediation pathway of financial self-efficacy was found to fail to bridge the influence of financial education, but was found to establish a significant indirect-only relationship of family environment and digital access on financial literacy. Originality/Value – The main novelty of this study lies in the role of family environment and digital access, which were shown to have no direct role, but became very significant when intervened by the psychological mediator factor of financial self-efficacy. The main message of this study is that individual financial mental maturity is an indirect-only mediation prerequisite for successful financial literacy adoption in the digital era.